Using a direct simulation Monte Carlo approach to model collisions in a buffer gas cell - supporting material - Heazlewood, B; Doppelbauer, M; Schullian, O; Rennick, C; Softley, T (University of Oxford, 2017)
The dataset includes results from our direct simulation Monte Carlo (DSMC) modelling of the collisions between buffer gas atoms and ammonia molecules within a buffer gas cell. Both elastic and inelastic collisions are considered, through the inclusion of energy-dependent state-to-state collision cross sections. The properties of the resulting molecular beam are examined as a function of cell parameters and operating conditions – yielding good agreement with available experimental measurements. This study represents an important extension of previous investigations into buffer-gas cooling. We demonstrate that thermalisation occurs well within the typical 10-20mm length of typical experimental buffer gas cells, suggesting that a shorter cell could be employed in many applications. Our DSMC calculations indicate that shorter cells would achieve comparable molecular beam properties (translational and rotational temperature) with the benefit of significantly increased molecular density. The data were created from 2015-2016 and are discussed in detail in the accompanying publication. The labelling of each data file corresponds to the labelling adopted for the associated figure in the publication